Climbing Dumbarton Rock: an exploration of climbers' experiences on sport and heritage from the perspective of existential authenticity. Issue 4 (1st October 2020) - Zhang, Yingying; McDowell, Matthew. L.
ABSTRACT: Dumbarton Rock represents elements of ancient and medieval Scottish history and has witnessed the prosperity (and decline) of industry. Meanwhile, the Rock plays an important role in Scottish climbing. Its sustainable development has caused much concern for those who love and care about it. Therefore, this research aims to study the meanings of the Rock from the perspective of rock climbing, through analyzing eight interviewees' experiences. It was found that the special location of the Rock seems to create a place of short-time isolation and liberty to the climbers. Its history and intensive difficulty also improve the climbers' experience and makes it a great attraction for them. Dumbarton Rock sits at the nexus of 'lifestyle'/'adventure'/'extreme' sport and Scottish heritage, and this article helps to provide a means by which to pursue qualitative research on existential authenticity in locations where sports tourism overlaps with that of heritage.